Regional Right Ventricular Function Assessed by Intraoperative Three-Dimensional Echocardiography Is Associated With Short-Term Outcomes of Patients Undergoing Cardiac Surgery - Keller, Marius; Duerr, Marcia-Marleen; Heller, Tim; Koerner, Andreas; Schlensak, Christian; Rosenberger, Peter; Magunia, Harry (Frontiers in Cardiovascular Medicine, 2022)
Background The assessment of right ventricular (RV) function in patients undergoing elective cardiac surgery is paramount for providing optimal perioperative care. The role of regional RV function assessment employing sophisticated state-of-the-art cardiac imaging modalities has not been investigated in this cohort. Hence, this study investigated the association of 3D echocardiography-based regional RV volumetry with short-term outcomes. Materials and Methods In a retrospective single-center study, patients undergoing elective cardiac surgery were included if they underwent 3D transesophageal echocardiography prior to thoracotomy. A dedicated software quantified regional RV volumes of the inflow tract, apical body and RV outflow tract employing meshes derived from 3D speckle-tracking. Echocardiographic, clinical and laboratory data were entered into univariable and multivariable logistic regression analyses to determine association with the endpoint (in-hospital mortality or the need for extracorporeal circulatory support). Results Out of 357 included patients, 25 (7%) reached the endpoint. Inflow RV ejection fraction (RVEF, 32 ± 8% vs. 37 ± 11%, p = 0.01) and relative stroke volume (rel. SV) were significantly lower in patients who reached the endpoint (44 ± 8 vs. 48 ± 9%, p = 0.02), while the rel. SV of the apex was higher (38 ± 10% vs. 33 ± 8%, p = 0.01). Global left and right ventricular function including RVEF and left ventricular global longitudinal strain did not differ. In univariable logistic regression, tricuspid regurgitation grade ≥ 2 [odds ratio (OR) 4.24 (1.66–10.84), p < 0.01], inflow RVEF [OR 0.95 (0.92–0.99), p = 0.01], inflow rel. SV [OR 0.94 (0.90–0.99), p = 0.02], apex rel. SV [OR 1.07 (1.02–1.13), p < 0.01] and apex to inflow rel. SV ratio [OR 5.81 (1.90–17.77), p < 0.01] were significantly associated with the endpoint. In a multivariable model, only the presence of tricuspid regurgitation [OR 4.24 (1.66–10.84), p < 0.01] and apex to inflow rel. SV ratio [OR 6.55 (2.09–20.60), p < 0.001] were independently associated with the endpoint. Conclusions Regional RV function is associated with short-term outcomes in patients undergoing elective cardiac surgery and might be helpful for optimizing risk stratification.